Education, the foundation for bridging the gap between science and society. A summary of the training processes supported in Honduras through the CGIAR Scaling for Impact Program in 2025 - Ayes Rivera, Irma; Duron Gallardo, Marlon; Martinez Castillo, Oscar; Guillen, Jose Francisco; Castellanos, Andrea; Martinez Baron, Deissy; Ramirez, Julian (2026)
Continuing the collaborative work that began in 2022 with AgriLAC Resilient in Honduras, and its ongoing scaling up through the CGIAR Impact Scaling Program, Climate Program and NORAD fundings, capacity building and development continued in 2025 in Honduras. This document is the summary of the training processes supported in Honduras through the CGIAR Scaling for Impact Program in 2025.